2021
DOI: 10.1016/j.cllc.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Features of Non–Small-Cell Lung Cancer in Young Patients

Abstract: Nonesmall-cell lung cancer (NSCLC) in young patients is rare. We retrospectively analyzed the presenting symptoms, clinicopathologic characteristics, and imaging features of 166 young patients with NSCLC. We found that young patients with NSCLC often present with nonspecific symptoms and have advanced disease at diagnosis, which can mimic other pathologies. Targetable genomic alterations are common and may drive imaging features. Background: Nonesmall-cell lung cancer (NSCLC) in young adult patients is rare, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Lung cancer is primarily a disease of the older population, with about 10% of patients <55 years at diagnosis (10). Several studies have revealed that younger patients with non-small cell lung cancer (NSCLC) represent a distinct clinico-biologic entity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Compared to older adults, young NSCLC patients are more likely to be women, Asians, or Pacific Islanders, have adenocarcinoma histology, and present with metastases (11)(12)(13)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is primarily a disease of the older population, with about 10% of patients <55 years at diagnosis (10). Several studies have revealed that younger patients with non-small cell lung cancer (NSCLC) represent a distinct clinico-biologic entity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Compared to older adults, young NSCLC patients are more likely to be women, Asians, or Pacific Islanders, have adenocarcinoma histology, and present with metastases (11)(12)(13)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…About 65% of patients who are diagnosed with AC are non-smokers. NSCLC remains the leading cause of cancer-related mortality in the United States and around the world ( Garrana et al, 2021 ). This cancer type is usually diagnosed in patients in the 6th and 7th decades of life, with less than 5% seen in patients below age 50 and even fewer below age 40 ( Sacher et al, 2016 ; Piccirillo et al, 2004 ; Jorgensen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC is extremely rare in young adults, who we defined developmentally between 18 and 35 years of age. Other cancers such as lymphoma, melanoma, sarcoma, breast and testicular cancers occur more frequently in this age group and are the leading cause of mortality in the young adult age group ( Garrana et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations